Plasma glutathione of HIV+ patients responded positively and differently to dietary supplementation with cysteine or glutamine - Borges-Santos, Maria Doroteia [UNESP]; Moreto, Fernando [UNESP]; Marques Pereira, Paulo Camara [UNESP]; Ming-Yu, Yong; Burini, Roberto Carlos [UNESP] (Elsevier B.V., 2012)
Objective: Patients with positivity for the human immunodeficiency virus (HIV) present low concentrations of antioxidant nutrients, including total glutathione (GSH) and its precursors. We investigated the responses of the sulfur-containing amino acid pathway to cysteine and glutamine (Gin) dietary supplements in patients with HIV compared with healthy controls.Methods: Twelve treated patients (six men and six women, 22-45 y old) and 20 healthy controls (10 men and 10 women, 20-59 y old) were randomly assigned to 7-d dietary supplements containing N-acetylcysteine (NAC; 1 g/d) or Gln (20 g/d), with a 7-d washout period ingesting their usual diet. Blood samples were drawn after an overnight fast. High-performance liquid chromatographic plasma analysis of sulfur-containing amino acids (methionine, homocysteine, cysteine, and taurine), GSH, oxidized GSH, and serine, glycine, glutamic acid, and Gln was carried Out moments before and after 7-d supplementations. Statistical comparisons were undertaken between groups and between dietary supplements (P < 0.05).Results: Patients with HIV showed higher oxidized GSH and lower concentrations of GSH and all amino acids except homocysteine. The HIV group responded to the NAC by increased levels of sulfur-containing amino acids and GSH and equalized taurine and GSH levels in the control group. The Gin supplements also equalized the levels of GSH, Gln, and glycine in the control group.Conclusion: An increase in GSH may be attained by NAC or Gln supplementation, with NAC acting by increasing cysteine levels and Gin likely acting by replenishing the glycine pool (trial registered at http://www.clinicaltrials.gov, identifier NCT00910442). (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Human immunodeficiency virus; Glutathione; Sulfur amino acids; N-acetylcysteine supplementation; Glutamine supplementation